Integrating fine‐scale seafloor mapping and spatial pattern metrics into marine conservation prioritization. Issue 8 (31st May 2020) - Proudfoot, Beatrice; Devillers, Rodolphe; Brown, Craig J.
Abstract: Marine protected area (MPA) planning often relies on scientific principles that help ensure that an area selected for conservation will effectively protect biodiversity. Capturing ecological processes in MPA network planning has received increased attention in recent years. High‐resolution seafloor maps, which show patterns in seafloor bio‐physical characteristics, can support our understanding of ecological processes. In part, owing to a global lack of high‐resolution seafloor maps, studies that aim to integrate seascape spatial pattern and conservation prioritization often focus on shallow biogenic habitats with less attention paid to deeper benthic seascapes (benthoscapes) mapped using acoustic techniques. Acoustic seafloor mapping strategies yield the spatial information required to extend conservation prioritization research into these environments, making incorporating seafloor ecological processes into conservation prioritization increasingly achievable. Here, a new method is proposed and tested that combines benthoscape mapping, landscape ecology metrics and a conservation decision support tool to prioritize areas with structural and potential connectivity value in MPA placement. Using a case study in eastern Canada, benthoscape composition and configuration were quantified using spatial pattern metrics and integrated into Marxan. Results illustrate how large patches of seafloor habitat in close proximity to neighbouring patches can be preferentially selected when benthoscape configuration is considered. The flexibility of the method for including relevant spatial pattern metrics or species‐specific movement data is discussed to illustrate how benthic habitat maps can improve existing conservation planning methods and complement existing and future work to support marine biodiversity conservation.